Chapter La componente romanza del lessico ucraino - Del Gaudio, Salvatore (Biblioteca di Studi Slavistici, 2019)
Ukrainian, unlike other East Slavic languages, is characterized by the active use of significant lexical components derived from Romance, Germanic, and West Slavic languages. This article presents a brief overview of the presence of Romance language lexical elements in Ukrainian and lays the groundwork for further research on the Ukrainian alloglot lexis and the comparison of Ukrainian with Russian and Belarusian.